'Endure and excuse': a mixed-methods study to understand disclosure of intimate partner violence among women living with HIV in Uganda. Issue 4 (6th April 2022) - Bloom, Brittnie E.; Hamilton, Kimberly; Adeke, Barbra; Tuhebwe, Doreen; Atuyambe, Lynn M.; Kiene, Susan M.
Abstract: Intimate partner violence and HIV remain significant health challenges among women living with HIV. Intimate partner violence has been linked to negative health outcomes and poorer HIV care engagement. This study examined intimate partner violence among Ugandan women living with HIV, their experiences disclosing such violence and how culturally normative factors affected disclosure-related outcomes. In a mixed-methods study conducted in Uganda in 2018, 168 women participated in interviewer-administered surveys; a sub-set who reported experiencing intimate partner violence participated in in-depth interviews (IDIs). Intimate partner violence was prevalent among women in the sample (68.0%); almost half experienced emotional violence (45.2%), while a smaller proportion had experienced physical (32.1%) and/or sexual violence (19.6%). Most women living with HIV (61.8%) had disclosed their experience of intimate partner violence to someone. Women who experienced intimate partner violence had higher odds of disclosure if they feared their partner and perpetrated violence against their partner. Thematic analysis of IDIs revealed enduring violence and blaming alcohol for men's perpetration of violence. Traditional cultural and gender norms, especially concerning motherhood and partnership, influenced women's experiences of intimate partner violence and disclosure. Multi-sectoral responses to challenge and reform cultural norms that perpetuate violence are needed, including mobilising key stakeholders (e.g. family, community, policy-makers) to serve as catalysts for change and encourage resource- and safety-seeking for women living with HIV to escape violence.